Breus’ mole/chorangiosis/chorangioma of the placenta: a dilemma with a rare fetal outcome report - Sobti, Nitika; Chandna, Ankita; Narula, Bhawna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Massive Subchorionic Thrombohematoma (MST) is a rare condition in which there is a massive collection of blood between the placental membranes and uterine wall separating the villous chorionic plate from villous chorion. It is relatively rare and is poorly understood. Many theories have been proposed to explain the etiology of Breus mole; some suggest it is a fetal haemorrhage, while others claim it has a maternal-origin thrombosis of placental vessels. A 30-year-old healthy Indian pregnant woman was presented at Max Hospital, Shalimar Bagh Delhi, India, during her second pregnancy with a complaint of fever. On routine level-2 ultrasonography (USG) done at 18.6 weeks of gestation showed thick placenta. No fetal tumours or any other anomalies were noted on that scan which was followed by a detailed scan which confirmed a solitary mass arising from fetal side 103x64x82 mm S/O chorioangioma. Serial growth and doppler USG were conducted to monitor placental function, tumor characteristics and future anatomy. The subject received steroids to enhance fetal lungs maturation at Week 30, iron/calcium supplements, Ecosprin tablets, and progesterone support. At 32.5 weeks, the subject developed deranged sugars followed by gestational hypertension at 34.1 weeks. Ultrasonography also showed fetal growth restriction with large chorioangioma. The subject underwent a successful elective caesarean section at 34.4 weeks. On placental examination, 10 cm large mass encasing ¾ of the placenta was identified as a large subchorionic hematoma/chorioangioma (800 g). This study concludes that early identification of a large chorangioma aids in consequent fetal surveillance, management of maternal symptoms, and delivery planning discussions even if the pathological diagnosis turns out to be Breus’ mole with underlying chorangiosis postnatally.